Akuntansi Bukan Sekadar Angka: Mengenal Profesi Akuntansi di Era Digital bagi Generasi Z - Rentor, Antonius Bimo; Kenisah, Melania Lintang; Patricia, Eva; Handayani, Risma (Joong-Ki : Jurnal Pengabdian Masyarakat, 2026)
The digital transformation has significantly changed the role of the accounting profession from routine bookkeeping to a strategic function that supports technology-driven decision making. However, many high school students still perceive accounting as merely recording and calculating financial transactions. This community service program aimed to improve students' understanding of the accounting profession, its transformation in the digital era, and career opportunities in the field. The program was conducted at Perguruan Advent Bandung involving 25 eleventh-grade students. Educational, inspirational, participatory, and practical approaches were implemented through lectures, interactive discussions, case studies, and question-and-answer sessions. Program effectiveness was evaluated using observations and questionnaires analyzed descriptively. The results indicated a 98% accuracy rate in participants' knowledge assessment. Participants also rated the learning materials (4.68/5) and speaker performance (4.72/5) highly. The program successfully enhanced students' awareness of accounting careers and demonstrated that community service activities can effectively strengthen accounting literacy among Generation Z.